The Application of Geometrical Method in Zukhruf Art Construction - Ya’acob, Ainun Jariah (2008)
This study investigates on the process of geometrical construction in Zukhruf Art. The construction of geometric used as the structure to construct the zukhruf. The term in process of constructing geometrical structure, whilst developing the zukhruf, will be employed as a method for mensuration and compositioning the zukhruf design. This study is conducted with technical artwork using AutoCAD software to assure the accuracy of geometrical construction. The following chapter are an attempt to explain the problem statement, that is comparison between manual process of zukhruf construction of Juzu’ 20 Al-Qur’an Mushaf Malaysia and digital process of geometrical construction in Zukhruf Art which using the “Theory of Square Repeat Unit and the Root Two System of Proportion”. This theory applied to generate the process of making geometric pattern. This study was conducted by using the primary and secondary sources of data method. Data collected from existing design (Juzu’ 20) were analyzed by dividing the circumference into 45o and 22.5o equal parts, which will determine the subsequent grid-patterns and repeat unit, while the radius of circle taken as a unit measure. The method of construction employed in constructing each part of zukhruf will be examined and computerized using AutoCAD software. The result indicates that the method of geometrical construction concluded as the main core of structural design form to construct the zukhruf. The geometric calculation contributes to the principle of balance, which was conceived as the basic law of creation. The development of zukhruf art derived based on the technique of geometric construction as the main of its structural basement. Contribution of the study analyzed pretend to establish the module and guideline of the design process, characterized by geometric construction and the law of composition as applied in Islamic Art through the mechanism of computer software technology.